Quality of Life: Mental and Physical Satisfaction after Abdominoplasty - Khan, Sikandar Ali; Ali, Ghazanfar; Tariq, Mohammad; shah, Muhammad Akmal; Ahmed, Muzafar; Aslam, Muhammad Sohail (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the impact of abdominoplasty on quality of life.Study Design: Cross-sectional study.Place and Duration of study: Psychiatry Department and Plastic Surgery Department, Combined Military Hospital, MultanPakistan, from Nov 2019 to Apr 2021.Methodology: We recruited 88 patients who were given a specifically designed proforma to fill before surgery and six months after the surgery. The proforma contained questions prepared to assess specific parameters. Demographic variables, general health, expectations from the operation, satisfaction with the outcome and any adverse outcomes of the operation were recorded. WHOQOL Bref for Life Satisfaction and the Patient Health Questionnaire (PHQ-4) were administered.Results: The mean patient age was 41.43±11.24 years. 68(78%) patients belonged to rural areas, while 19(22%) were from urban dwellings. Regarding body mass index (BMI), 43(49.6%) patients had obesity Class-I, 33(37.4%) were overweight, 8(9.4%) had obesity Class-II, and only 4(3.6%) fell into the category of obesity Class-III. There was high satisfaction post-operatively after abdominoplasty surgery. There were improvements in Quality of Life (p